2018
DOI: 10.20982/tqmp.14.3.r001
|View full text |Cite
|
Sign up to set email alerts
|

The incremental validity of the Triarchic model of psychopathy in replicating "The dark side of love and life satisfaction: Associations with intimate relationships, psychopathy and Machiavellianism"

Abstract: The present study is a replication of Ali and Chamorro-Premuzic (2010) [The dark side of love and life satisfaction: Associations with intimate relationships, psychopathy and Machiavellianism. Personality and Individual Differences, 48(2), 228-233]. We replicated the previous findings, supporting the significance of psychopathy and relationship components as predictors of life satisfaction, and extended our findings to the dark triad and the triarchic model of psychopathy. Our results suggest that the triarchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…It is supposed that the divergence in findings of the study by Tozar and this current study arises from differences in sampled groups. Several studies performed in Europe found that there was a relationship between narcissism and life satisfaction levels (Bourbonnais & Durand 2018;Aghababaei & Blachnio 2015). When these statistical findings are assessed on the basis of life satisfaction and narcissistic personality traits, it is thought that it is normal to obtain this result because narcissistic individuals enjoy life better along with being at the forefront and fulfilling their aspirations.…”
Section: Discussionmentioning
confidence: 99%
“…It is supposed that the divergence in findings of the study by Tozar and this current study arises from differences in sampled groups. Several studies performed in Europe found that there was a relationship between narcissism and life satisfaction levels (Bourbonnais & Durand 2018;Aghababaei & Blachnio 2015). When these statistical findings are assessed on the basis of life satisfaction and narcissistic personality traits, it is thought that it is normal to obtain this result because narcissistic individuals enjoy life better along with being at the forefront and fulfilling their aspirations.…”
Section: Discussionmentioning
confidence: 99%